2017
DOI: 10.1016/j.neuroscience.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acid biostatus, phospholipase A2 activity and brain white matter microstructure across adolescence

Abstract: Adolescence is a period of major brain white matter (WM) changes, and membrane lipid metabolism likely plays a critical role in brain WM myelination. Long-chain polyunsaturated fatty acids (LC-PUFAs) are essential components of cell membranes including oligodendrocytes, and LC-PUFA release and turnover in membranes is regulated by phospholipase A2 enzymes. To investigate the role of membrane lipid metabolism in healthy WM myelination across adolescence, the present study examined the relationship between membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 58 publications
2
11
0
1
Order By: Relevance
“…Omega-3 (n-3) PUFAs including docosahexaenoic acid (DHA) and the omega-6 PUFA arachidonic acid (AA) have opposing effects on immuneinflammatory signaling, and metabolites of DHA have inflammation-resolving properties [16][17][18][19][20][21]. Importantly, emerging evidence suggests that PUFAs are associated with WMI in healthy subjects [22][23][24] and in patients with psychiatric disorders [25,26]. Meta-analyses indicate that schizophrenia [27], bipolar disorder [28], and unipolar depression [29] are associated with PUFA deficits including DHA.…”
mentioning
confidence: 99%
“…Omega-3 (n-3) PUFAs including docosahexaenoic acid (DHA) and the omega-6 PUFA arachidonic acid (AA) have opposing effects on immuneinflammatory signaling, and metabolites of DHA have inflammation-resolving properties [16][17][18][19][20][21]. Importantly, emerging evidence suggests that PUFAs are associated with WMI in healthy subjects [22][23][24] and in patients with psychiatric disorders [25,26]. Meta-analyses indicate that schizophrenia [27], bipolar disorder [28], and unipolar depression [29] are associated with PUFA deficits including DHA.…”
mentioning
confidence: 99%
“…While myelin impairment is a marker of most if not all neurodevelopmental disorders (Aoki et al, 2017; Kochunov et al, 2017), only little is known about the role of n‐3 PUFAs in the developmental myelination process. Some preclinical studies showed positive results with n‐3 LC‐PUFA supplementation on the maturation of oligodendrocytes and the expression of myelin related genes (Bernardo et al, 2017; Feltham et al, 2019; McNamara et al, 2017; Salvati et al, 2008; Siegert et al, 2017; Silva et al, 2017; Tian et al, 2011), yet others reported detrimental effects (Church et al, 2008; Church et al, 2009; Haubner et al, 2007). Moreover, clinical studies revealed a strong correlation between white matter integrity and n‐3 PUFA content in preterm infants, psychotic or aged subjects (Gu et al, 2016; Peters et al, 2009; Peters et al, 2013; Peters et al, 2014; Witte et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Enfin, une étude suggère d'une part que la myélinisation du cerveau à l'adolescence chez des sujets sains est corrélée négativement à l'activité de la phospholipase A2 intracellulaire et d'autre part que la concentration en DHA est corrélée positivement avec la myélinisation du corps calleux [43].…”
Section: Troubles Cognitifs Et Oméga-3 Dans La Schizophrénieunclassified